Medication adherence among multimorbid individuals in Saudi Arabia - Haifa Alturki; Nawaf Alnuwaysir; Ghaya Almutairi; Shahad Alonazi; Rayouf Al Otaibi; Reham Alharbi; Joury Dabbour (Eastern Mediterranean Health Journal, 2026)
Background: Multimorbidity is increasingly common among adults in Saudi Arabia. As treatment regimens become more complex, medication adherence becomes more challenging. Understanding the behavioural drivers of non-adherence is essential to improving outcomes and reducing preventable complications. Aim: To assess the prevalence of medication adherence among individuals aged ≥45 with multimorbidity, examine the association between the number and type of chronic conditions and adherence, and identify key reasons behind nonadherence. Method: Between March and May 2025, we interviewed 339 Saudi adults aged ≥45 with ≥2 chronic conditions. The data was analysed using SPSS version 28. Reliability testing was performed using Cronbach’s alpha, Fisher’s Exact Test and binary logistic regression were used to assess associations between adherence and other variables. P < 0.05 was considered statistically significant. Results: Only 14.7% of the study participants were adherent to their medication. Significant associations were found between adherence and age, education, heart disease, and anaemia. Adults aged 45–54 years had higher odds of nonadherence than those aged 65+ years (OR = 3.78, 95% CI: 1.36–10.49, P = 0.01), and participants with a bachelor’s degree or higher had higher odds of non-adherence (OR = 3.51, 95% CI: 1.24–9.95, P = 0.01). Having a heart disease was linked to better adherence (OR = 0.45, 95% CI: 0.23–0.86, P = 0.02), whereas having anaemia predicted non-adherence (OR = 7.19, 95% CI: 0.96–53.68, P = 0.02). The most common reasons for non-adherence were poor refill planning (68.1%) and skipping medication when feeling better (22.1%). Conclusion: Medication non-adherence among multimorbid adults in Riyadh was alarmingly high (>85%). Interventions should address behavioural barriers, refill planning and establishment of reminder systems.